1995
DOI: 10.1111/j.1600-0625.1995.tb00058.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine and protease levels in healing and non‐healing chronic venous leg ulcers

Abstract: Leg ulcers present a common and recurring problem in older people creating discomfort and distress for the patient and a great cost to the health care services. Cultured keratinocyte grafts have been used by many investigators to stimulate healing of chronic venous ulcers. It has been proposed that they may do this by producing cytokines which modulate the healing process. However, the types and levels of cytokines in the leg ulcer fluid before and during healing are not known. Wound fluid was collected from v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
4
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(110 citation statements)
references
References 23 publications
3
96
4
2
Order By: Relevance
“…38 In this study, GM-CSF was administered at concentrations from 0.1 to 75 g/mL, representing values 5,000 to 4 million times higher, although the local endogenous GM-CSF levels rise about 100-fold at an inflammatory site to 1,000 to 3,000 pg/mL. 15,33,39 In the study by Ure et al, 15 intradermal injections in the thigh of healthy volunteers with 20 g GM-CSF 1 and 4 days after wounding resulted in elevated GM-CSF levels not only in the treated leg but also (albeit less so) in the wound on the contralateral leg not injected with GM-CSF. This finding supports our biochemical data of reduced collagen deposition also in the control ePTFE tubes as a distant effect of GM-CSF.…”
Section: Discussionmentioning
confidence: 97%
“…38 In this study, GM-CSF was administered at concentrations from 0.1 to 75 g/mL, representing values 5,000 to 4 million times higher, although the local endogenous GM-CSF levels rise about 100-fold at an inflammatory site to 1,000 to 3,000 pg/mL. 15,33,39 In the study by Ure et al, 15 intradermal injections in the thigh of healthy volunteers with 20 g GM-CSF 1 and 4 days after wounding resulted in elevated GM-CSF levels not only in the treated leg but also (albeit less so) in the wound on the contralateral leg not injected with GM-CSF. This finding supports our biochemical data of reduced collagen deposition also in the control ePTFE tubes as a distant effect of GM-CSF.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies on cytokine levels in wound fluids from CVLUs have been conducted, but results are inconclusive and more studies are warranted [3,[12][13][14][15][16]. In particular more knowledge is needed on how different cytokines are expressed in chronic wounds at different time-points during the healing process.…”
Section: Introductionmentioning
confidence: 99%
“…Studies comparing acute and chronic wounds have demonstrated that differences between them do exist, and it is possible that these differences become more dramatic as a wound ages, eventually reaching a critical point at which healing is less likely to occur. [41][42][43][44][45][46][47] The relationship between wound duration and wound size is further complicated by an interaction between these 2 risk factors. A basic assumption inherent in regression models is that the association of any given variable with the outcome is the same for all values of any other given variable.…”
mentioning
confidence: 99%